Digital filter and clustering algorithms for improving energy resolution of CdZnTe detectors. (22nd November 2011) - Shaaban, Noha
CdZnTe (CZT) detectors are promising detectors especially for portable gamma spectroscopy and safeguards applications. However, energy resolution of CZT is suffering from poor mobilities of charge carriers, which result in a large signal shape variations depending on the interaction position inside the detector. Clustering technique was used to classify and independently treat these shape variations. Before the classification process, a digital filter was used to remove noises from CZT signals. The filtered signals were classified using Maxi-Mini Distance algorithm. Much improvement was obtained in the energy resolution of the CZT after the classification of the filtered signals than the unfiltered signal.